Challenges toward the E-marketing faced in Bangladesh Telecommunication firms: An investigative study on selected Tele-firms in Bangladesh - Md. Amran Hossain; Ankit Katrodia (AMAR (Andalas Management Review), 2026)
In Bangladesh, the telecommunications system has become highly competitive due to the liberalization of the sector to improve communication there. Despite the success, the telecommunications industry in Bangladesh faces several impediments that have hindered firms' efforts to achieve their goals, attracting scholars' attention to foster a shared understanding for effective strategic formulation to overcome them. The findings support the importance of conducting a survey among six selected telecommunication companies in Bangladesh: Airtel, Grameenphone (Telenor), Banglalink, Robi, BTCL, and Tele-talk. The data was collected from the employees and users through interviews and questionnaires. This Hypothesis study was analyzed and tested by SPSS, namely Hypothesis Test for Proportions, Proportion Chi-Square Test, Correlation Coefficient, Regression, and t-test models. Bangladeshi tele-industry faces many challenges, such as mismanagement of e-marketing channels, the inappropriate incorporation of marketing strategies with consumers, and improper communication and social behavior by telecommunication brands. This study was believed to be an important and reliable source of literature reviews and to have created an alert on E-marketing deficits in the Bangladesh Tele-industry for strategic goals.